2021
DOI: 10.3389/fmed.2021.717168
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Randomized Controlled Trial to Investigate Whether Zoledronate Prevents Bone Loss After Discontinuation of Denosumab: The Study Protocol of Denosumab Sequential Therapy (DST) Trial

Abstract: Background: Though denosumab is an effective treatment for osteoporosis, the rebound effect after discontinuation has drawn investigators' attention. It includes a dramatic loss of gained bone mineral density (BMD) and an increased risk of vertebral fractures. This prospective multi-institutional randomized controlled trial aims to investigate whether zoledronate prevents loss of BMD after discontinuation of denosumab. The trial was registered as Denosumab Sequential Therapy (DST) trial in March 2019 at clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…This is a similar protocol to the DST (denosumab sequential therapy) trial where a single infusion of IV zoledronate was given at 6 months and the timing of a second infusion based on CTX levels. 8 Similarly, a randomised controlled trial by Sølling et al, 9 treated patients with zoledronate at either 6 months after the last dose of denosumab, 9 months after, or when CTX bone marker was elevated above 1.26 µg/L (2× upper limit of normal in premenopausal women). The trial concluded that a single zoledronate infusion did not fully protect against loss in BMD but that the recommendation would be for an infusion 6 months after discontinuing denosumab.…”
Section: Discontinuation Of Denosumab After 2 or More Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a similar protocol to the DST (denosumab sequential therapy) trial where a single infusion of IV zoledronate was given at 6 months and the timing of a second infusion based on CTX levels. 8 Similarly, a randomised controlled trial by Sølling et al, 9 treated patients with zoledronate at either 6 months after the last dose of denosumab, 9 months after, or when CTX bone marker was elevated above 1.26 µg/L (2× upper limit of normal in premenopausal women). The trial concluded that a single zoledronate infusion did not fully protect against loss in BMD but that the recommendation would be for an infusion 6 months after discontinuing denosumab.…”
Section: Discontinuation Of Denosumab After 2 or More Dosesmentioning
confidence: 99%
“…We subsequently measure CTX 6 months later to determine if a second short interval dose of zoledronate is required. This is a similar protocol to the DST (denosumab sequential therapy) trial where a single infusion of IV zoledronate was given at 6 months and the timing of a second infusion based on CTX levels 8 . Similarly, a randomised controlled trial by Sølling et al, 9 treated patients with zoledronate at either 6 months after the last dose of denosumab, 9 months after, or when CTX bone marker was elevated above 1.26 µg/L (2× upper limit of normal in premenopausal women).…”
Section: Discontinuation Of Denosumab After 2 or More Dosesmentioning
confidence: 99%